2019
DOI: 10.1155/2019/3827360
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microbial Communities in a Dairy Farm Matrix in Ningxia, China, by 16S rDNA Analysis

Abstract: A large amount of dairy manure is produced annually in the Ningxia Hui Autonomous Region of China due to the increase in food-producing animal agriculture in this region. The presence of bovine-originated zoonotic, especially human, pathogenic bacteria in untreated manure poses a significant threat to the environment and to public health. However, little is known about the composition, diversity, and abundance of bacterial communities in untreated dairy manure in the Ningxia region. In this study, the microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…All samples, regardless of the environmental type, were dominated by four bacterial phyla: Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidetes. This is largely consistent with prior studies that showed the predominance of the four bacterial phyla in cow and pig stables and indoor home environments ( Hong et al, 2012 ; Boissy et al, 2014 ; Zhang et al, 2019 ). The higher abundance of Firmicutes and lower abundance of Proteobacteria in farmers’ homes relative to suburban homes is basically in line with prior epidemiological findings suggesting that Firmicutes decrease the risk of atopic sensitization ( Lee et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…All samples, regardless of the environmental type, were dominated by four bacterial phyla: Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidetes. This is largely consistent with prior studies that showed the predominance of the four bacterial phyla in cow and pig stables and indoor home environments ( Hong et al, 2012 ; Boissy et al, 2014 ; Zhang et al, 2019 ). The higher abundance of Firmicutes and lower abundance of Proteobacteria in farmers’ homes relative to suburban homes is basically in line with prior epidemiological findings suggesting that Firmicutes decrease the risk of atopic sensitization ( Lee et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%